Authentic Assessment in Islamic Education - Mimi Musmiroh Idris; Abas Asyafah (Islamic Research, 2020)
This study is a literature study that discusses authentic assessment in the learning of Islamic religious education. Assessment that has been used in the assessment process at school is a traditional assessment, which tends to assess cognitive aspects, and ignores the affective and psychomotor aspects. Assessment should be able to assess all aspects, namely attitudes, skills, and knowledge. The purpose of this paper is to describe authentic assessments in the learning of Islamic Religious Education. The results of this study are descriptions of authentic assessments as an evaluation process of learning outcomes and student performance in applying it in real life. This is considered important because students are challenged to apply their knowledge and skills in real situations. This is because through authentic assessment teachers can also find out the extent of students' understanding and ability. With authentic assessment, the teacher will know the development of students from the data collected. In the use of authentic assessment, teachers are recommended to be able to operate computers, because the assessment format uses rubrics, and the teacher must also be prepared by making assessment formats used to evaluate students.